The faunal assemblage in the Mesolithic to the Chalcolithic/Bronze Age levels at Lumentxa (Lekeitio, Bizkaia, northern Iberian Peninsula). (2nd September 2022) - Suárez-Bilbao, Aitziber; Garcia-Ibaibarriaga, Naroa; Castaños, Pedro; Murelaga, Xabier; Berganza, Eduardo; Arribas, José Luis
ABSTRACT: A systematic study of vertebrate remains from Mesolithic to Chalcolithic/Bronze Age levels in Lumentxa Cave has examined a total of 12, 390 remains belonging to large mammals, small mammals, amphibians and reptiles, which have been identified at genus/species level. They are distributed among 37 taxa, corresponding to a minimum number of 328 individuals. The analysis of the fauna has allowed the reconstruction of the lifestyle of the human groups that inhabited Lumentxa, and which originated part of the large mammal accumulation from the Neolithic to Bronze Age periods. Changes in food production, in natural resource management and in settlement patterns originated a new way in which humans and the environment interacted.